V rutse leta - Aleksandrov, Evgeny (Russia, 2005)
The Southern part of the Ural Mountains, 2004. The town of Miass used to be known as one of the gold mining and steel work centers of the Southern Ural. Old believers started to settle in this region as early as the eighteenth century. They brought with them and have kept ever since their ancient religious and cultural traditions. The anti-clerical campaign unleashed by the Soviet regime from the 1920s made the monks painfuly aware of the fragility of their cultural legacy, prompting many to popularize their knowledge among the lay audiences. For instance, the films shows a local parioshioner at the Church of Protection of the Most Holy Mother of God demonstrating specific techniques of writing musical scripts employed for recording psalms and religios chants, one of which she performes. She was taught to read the notes by a nun called Minadora. Minadora also shares her knowledge of the ancient art of "Вруцелето" - calculating the dates of Orthodox feasts on the joints and fingers of a palm.
Keywords: Documentary films